The effect of using technology task based approach on english language achievement among primary four school students in Nigeria - Hussaini, Iliyasu (2017)
Learning English is essential in Nigeria because English is used as the medium of instruction and also taught as a subject in all Nigerian schools. Most of the school curriculum's are planned and communicated in English, but the poor performance of students in English at primary level has raised a lot of concern. This failure is attributed to teachers method of language teaching. Therefore, an English teaching approach was developed based on three (3) different methods (CALL, TBLT & P-GENRE) named as Technology Task Based Approach (TTBA). This study aimed to investigate the effect of TTBA on English proficiency skills in Nigerian primary schools. A quasi-experimental was employed as the research design in this study. The respondents of the study consisted of 62 primary school students in Nigerian primary schools that fonn into two (2) groups which were experimental group and control group. The experimental group was instructed using TTBA while the control group was taught using the traditional method. The period of the treatment lasted for eight (8) weeks. The collected data through pre-test and post-test was analyzed by using independent t-test and paired sample test at .05 level of significance. The findings of the study indicated that there is a significant effect of TTBA on the students' reading, speaking and writing skills. The results of the study revealed statistically significant differences in scores between the experimental group and control group. The result also showed that teachers and students have positive attitudes towards the application of TTBA. This teaching approach also proved that it is able to enhance students' interest in studying English. Thus, it is recommended that primary school students should reflect on the tasks, strategies, and activities of learning in TTBA and apply them in learning English. Primary school teachers should integrate tasks with technology in language teaching to improve students' language proficiency skills. Teachers should encourage students to join in the tasks and group activities with interest and attentiveness. Meanwhile the Nigerian Ministry of Education should organize teacher training on how to apply TTBA in language teaching.